ZVS/ZCS Vienna rectifier topology for high power applications - Ali, Abdar; Mansoor Khan, Muhammad; Yuning, Jiang; Ali, Yaqoob; Faiz, Muhammad Talib; Chuanwen, Jiang (IET power electronics, 2019)
This paper focuses on the study of a soft‐switched unidirectional boost‐type rectifier employing a snubber circuit, used as a front‐end converter stage in high‐power applications. The proposed rectifier operates with soft switching which results in high efficiency and low cost. The switching losses and electromagnetic interference (EMI) result in poor efficiency, therefore, soft switching techniques need to be developed to improve the efficiency. To achieve the desired result, the snubber circuit which consists of a lossless snubber switch cell and a resonant inductor, is introduced in the above‐mentioned converter. The topology of the proposed converter is derived from the conventional T‐type three‐level boost rectifier. The circuit operation, theoretical analysis, and simulation of the converter in MATLAB/Simulink environment are carried out. Finally, a 10 kW laboratory set‐up of the proposed soft‐switched unidirectional rectifier is built. The experimental results obtained validate the theoretical analysis of the circuit.